Efficacy of high-frequency repetitive transcranial magnetic stimulation in schizophrenia patients with treatment-resistant negative symptoms treated with clozapine - Wagner, Elias Maximilian; Wobrock, Thomas; Rietschel, Marcella (Schizophrenia research, 2019)
Background - Repetitive transcranial magnetic stimulation (rTMS) is a promising augmentation treatment for schizophrenia, however there are few controlled studies of rTMS augmentation of clozapine. - Methods - Using data from the ‘rTMS for the Treatment of Negative Symptoms in Schizophrenia’ (RESIS) trial we examined the impact of rTMS on PANSS total, general, positive and negative symptoms among participants on clozapine. rTMS was applied to the left dorsolateral prefrontal cortex (DLPFC) for five treatment sessions/week for 3-weeks as augmentation for patients with a predominant negative syndrome of schizophrenia, as rated on PANSS. - Results - 26 participants from the RESIS trial were on clozapine, receiving active (N=12) or sham (N=14) rTMS treatment. In our Linear Mixed Model (LMM) analysis, time×group interactions were significant in the PANSS positive subscale (p=0.003) (not being the corresponding behavioral output for DLPFC stimulation), the PANSS general subscale (p<0.001), the PANSS total scale (p=0.015), but not the PANSS negative subscale (p=0.301) (primary endpoint of the RESIS trial), when all PANSS measurements from screening to day 105 were included. Descriptive data suggests that in the active group the improvement was more pronounced compared to the sham rTMS group. - Conclusions - In this largest available clozapine cohort, active rTMS may be more effective than sham rTMS when added to clozapine for positive and total psychotic symptoms. These findings should be interpreted with caution given this is a secondary analysis with a limited number of participants.